2011
DOI: 10.1299/jfst.6.765
|View full text |Cite
|
Sign up to set email alerts
|

Direct Numerical Simulation of Impinging Shock Wave/Transitional Boundary Layer Interaction with Separation Flow

Abstract: The interaction of a spatially transitional boundary layer flow at freestream Mach number M = 2.0 with an impinging oblique shock wave (β = 35.56) is studied by means of direct numerical simulation (DNS). High amplitude (5%) three-dimensional isotropic disturbances are superimposed on the laminar profile for a Reynolds number based on the boundary layer displacement thickness of Re δ*0 = 1000 at the inlet plane of the computational box. Under the selected flow conditions, the interaction of the boundary layers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…The simulation domain was found to be of insufficiently large enough scale to capture any large-scale shock motion and, therefore, the agreement between experimental and computational data was limited. An oblique SBLI at Mach 2.0 and Re δ * θ = 1000 was predicted using DNS by Tokura and Maekwa (2011). Good agreement between previous studies was found, although comparisons were limited due to the low Reynolds number used in the study.…”
Section: Computational Studies Of Sblissupporting
confidence: 55%
See 2 more Smart Citations
“…The simulation domain was found to be of insufficiently large enough scale to capture any large-scale shock motion and, therefore, the agreement between experimental and computational data was limited. An oblique SBLI at Mach 2.0 and Re δ * θ = 1000 was predicted using DNS by Tokura and Maekwa (2011). Good agreement between previous studies was found, although comparisons were limited due to the low Reynolds number used in the study.…”
Section: Computational Studies Of Sblissupporting
confidence: 55%
“…Nevertheless, a broad variety of SBLI problems have been tackled using a range of computational methods with varying degrees of success (Bhagwandin & DeSpirito, 2011;Dolling, 2001;Oliver et al, 2007). These methods have included various forms of Reynolds Averaged Navier Stokes (RANS) approaches (DeBonis et al, 2010;Thivet, 2002;Vallet, 2007), unsteady RANS (URANS) (Barakos, Doerffer, Hirsch, Dussauge, & Babinsky, 2010;Hirsch, 2010a;Sandham, 2010), Detached Eddy Simulations (DES) (Garnier, 2009;Shams & Comte, 2010), Large Eddy Simulations (LES) (DeBonis et al, 2010;Eagle, Driscoll, & Benek, 2012;Hadjadj, 2012) and Direct Numerical Simulations (DNS) (Adams, 2000;Tokura & Maekwa, 2011). Clearly these methods provide different levels of modeling fidelity and sophistication along with concomitant resource demands.…”
Section: Computational Studies Of Sblismentioning
confidence: 99%
See 1 more Smart Citation
“…where t is the time, is a Cartesian coordinate system, is the density, is the velocity vector, is the thermodynamic pressure, related to the density and temperature T by the dimensionless form of the perfect gas law, and is the total energy which is defined as (Tokura et al, 2011…”
Section: Numerical Methods 21 Governing Equations and Discretization mentioning
confidence: 99%